Public Investments to Development of Irrigation System and Main Enlightenment Issues of Climate Change Adaptation in Agriculture of Azerbaijan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Climate change mitigation and adaptation strategy is one of the seventh goals of the Sustainable Development Goals committed by more than 190 leaders in 2015 year. Adaptation strategy in agriculture involves different options and actions by producers and public agencies seeking to maximize public good aspects of adaptation. Public investment to irrigation system of Azerbaijan is vital for country where only 1/3 of all agricultural lands are irrigated and arable. Besides this the water resources in Azerbaijan are very limited and country annually using the 70% of all renewable natural water recourses. Annual water shortage in Azerbaijan varies between 4.5-5 billion m3. The public financial capital should be invested to irrigation system of country as a part of national adaptation program. Public investments to climate change adaptation strategies should aim at maintaining, or even increasing, food production in key exporting developed and developing regions, or in regions key to regional food security.